2010
DOI: 10.1239/jap/1269610829
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Allocation of Active Redundancies to k-out-of-n Systems with Heterogeneous Components

Abstract: In this note we deal with the allocation of independent and identical active redundancies to a k-out-of-n system with the usual stochastic order among its independent components. The optimal policy is proved both to assign more redundancies to the weaker component and to majorize all other policies. This improves the corresponding one in Hu and Wang (2009) and serves as a nice supplement to that in Misra, Dhariyal and Gupta (2009) as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…A relevant problem in reliability theory is to determine the optimal replacement policy (under different criteria) for the components in a given system structure. Many results have been obtained under the assumption of independent components (see, eg, Barlow & Proschan, 1975;Belzunce, Martínez-Riquelme, & Ruiz, 2018;Boland & El-Neweihi, 1995;Chahkandi et al, 2016;Boland, El-Neweihi, & Proschan, 1992;Li & Ding, 2010;Natvig, 2011;Shaked & Shanthikumar, 1992). Different assumptions have been made for the redundant components.…”
Section: Introductionmentioning
confidence: 99%
“…A relevant problem in reliability theory is to determine the optimal replacement policy (under different criteria) for the components in a given system structure. Many results have been obtained under the assumption of independent components (see, eg, Barlow & Proschan, 1975;Belzunce, Martínez-Riquelme, & Ruiz, 2018;Boland & El-Neweihi, 1995;Chahkandi et al, 2016;Boland, El-Neweihi, & Proschan, 1992;Li & Ding, 2010;Natvig, 2011;Shaked & Shanthikumar, 1992). Different assumptions have been made for the redundant components.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, one may wonder how close the two allocation numbers should be. According to Li and Ding (), for k‐out‐of‐n systems with independent base component lifetimes X1ststXn and i.i.d. redundancy component lifetimes YistX1, i=1,,m, if all redundancy components are assigned to two base components Xk and X, then the strategy (rk,r) such that r1rkr is the optimal one.…”
Section: Optimal Allocation Strategy For Symmetric Systemsmentioning
confidence: 99%
“…Recently, Li and Ding [9] proved in the following result that more redundancies should be allocated to the component with stochastically smaller lifetime under the framework that redundancies are i.i.d. and the working components are independent.…”
Section: Multiple Active Redundanciesmentioning
confidence: 99%
“…active redundancies allocated to a series system with n independent stochastically ordered components, Misra et al showed that the lifetime of the resulting series system has a survival function Schur‐concave with respect to r in {}(r1MathClass-punc,MathClass-rel⋯MathClass-punc,rn) MathClass-punc: r1 MathClass-rel⋯ rnMathClass-punc,r1 MathClass-bin+ MathClass-rel⋯MathClass-bin+ rn MathClass-rel= mMathClass-punc,ri MathClass-rel∈ NMathClass-punc,i MathClass-rel= 1MathClass-punc,MathClass-rel⋯MathClass-punc,n. Afterward, Li and Ding further investigated the allocation of m active redundancies and deduced that allocating more redundancies to the weaker component will stochastically increase the system's lifetime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation